World Digital Library.
The World Digital Library (WDL) makes available on the Internet, free of charge and in multilingual format, significant primary materials from countries and cultures around the world. The principal objectives of the WDL are to: Promote international and intercultural understanding; Expand the volume and variety of cultural content on the Internet; Provide resources for educators, scholars, and general audiences; Build capacity in partner institutions to narrow the digital divide within and between countries.
Keywords: Beelddatabank; Encyclopedieën